2021
DOI: 10.3390/ijerph18115842
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Changed Use of Greenspace during COVID-19 Pandemic on Depression and Anxiety

Abstract: The COVID-19 pandemic has had devastating consequences for health, social, and economic domains, but what has received far less focus is the effect on people’s relationship to vital ecological supports, including access to greenspace. We assessed patterns of greenspace use in relation to individual and environmental factors and their relationship with experiencing psychological symptoms under the pandemic. We conducted an online survey recruiting participants from social media for adults in Korea for September… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 63 publications
6
50
0
2
Order By: Relevance
“…Indeed, more and more literature documents how people’s interactions with green space changed during the COVID-19 pandemic. Some studies report decreased levels of green space exposure during the pandemic [ 14 16 ], whereas others report that the duration and frequency of green space visits increased during the pandemic [ 17 20 ]. Evidence indicates that interactions with green spaces might vary based on the stringency of lockdown policies, socioeconomic status, and work flexibility [ 16 , 17 ] how far away the green space is [ 21 , 22 ], or potentially due to differences in lockdown policies in different places [ 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, more and more literature documents how people’s interactions with green space changed during the COVID-19 pandemic. Some studies report decreased levels of green space exposure during the pandemic [ 14 16 ], whereas others report that the duration and frequency of green space visits increased during the pandemic [ 17 20 ]. Evidence indicates that interactions with green spaces might vary based on the stringency of lockdown policies, socioeconomic status, and work flexibility [ 16 , 17 ] how far away the green space is [ 21 , 22 ], or potentially due to differences in lockdown policies in different places [ 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nature contact estimates from "big data" datasets (e.g., Google mobility, Strava, Geotagged Instagram images) did not provide precise definitions of 'natural environments', may have counted multiple visits by the same individuals and might not be representative of the larger population due to inability to obtain data from individuals who are not either using the apps or sharing their location information. All the big data studies identified in this review revealed considerable increases in nature contact (Lu et al, 2021b;Rice and Pan, 2021;Venter et al, 2020), whereas smaller datasets (e.g., survey data) utilized by studies in this review reported mixed findings regarding nature contact during the lockdown (Grima et al, 2020;Heo et al, 2021;Ugolini et al, 2021). Rice and Pan (2021) emphasized the need to validate big data inferred changes in nature visitation.…”
Section: Opportunities For Nature Exposurementioning
confidence: 89%
“…Most of these studies identified that during the lockdown period, the frequency of visiting nature and spending time outdoors increased compared to before lockdown. However, one-in-three studies found that nature contact decreased during the lockdown (Ugolini et al, 2021;Burnett et al, 2021;Heo et al, 2021). There may be several reasons for the contrasting findings regarding nature contact during the COVID-19 lockdown.…”
Section: Opportunities For Nature Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…During the lockdown period many people experienced a higher level of psychological stressors, both in frequency and intensity, leading to potentially harmful interpersonal and environmental stimuli, including domestic violence and abuse, as well as deteriorating family relationships [89,90]. Sections of the community, such as older people, people with poor mental health, people with disability, people with non-communicable diseases, people who were homeless, people living on their own, and people with reduced communication and limited social networks beyond their work settings, were disproportionately at risk [90,91], with the pandemic both exacerbating existing mental health conditions [91][92][93][94] and creating and intensifying inequalities [89,[94][95][96][97].…”
Section: Lessons From the Covid-19 Pandemicmentioning
confidence: 99%